PENGARUH TERPAAN TAYANGAN VLOG ARIEF MUHAMMAD DI YOUTUBE TERHADAP MINAT MEMBUAT VLOG PADA KOMUNITAS YOUTUBERS MINANG - Ryzka Aulia Nissya; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
One of the social media outlets featured videos is Youtube. Video content can be accessed on Youtube from music, movies, news & information, sports,lifestyles,games and vlogs. A vlog is a video containing opinions, stories or daily activities that are usually posted on blogs. One of the vlogs used as research is the vlog of Arief Muhammad’s alleged intention of creating a vlog on Minang creator’s content community called the Youtuber Minang Community.          This study use the New Media theory in order to find out how big the responder’s response is to Arief Muhammad’s image, to determine the response of the respondents to the interest of creating a vlog on the Youtubers Minang Community and to analyze Arief Muhammad’s influence on Youtube to create vlog on the Youtubers Minang Community. This type of research is a quantitative study with descriptive and explanatory methods using the purposive sampling and unknown population formula that calculations came to be 105 respondents. Researchers collect data with questionaires and data processing assisted by using the Windows 24 SPPS program.This study shows that level the effect of exposure to Arief Muhammad vlog shows on Youtube on interest in making vlogs in the Youtubers Minang Community are moderate. This is seen from the simple linear regression analysis in this research getting that result Y =4,321 + 0,761X which means constant value (α) 4,321. This mean that if an X is 0 the interest then the vlog (Y) is worth 4,321. In the meantime value t count = 10,594 > t table = 1,98326 with significance 0,00 < 0,05. Based on the value of Rsquare by 0,521, it means that there is an influence between Arief Muhammad’s shadow of blame on the interest of creating the vlog network on Youtuber Minamg with an influence of 52,1% and the remainder of which is 47,9% influenced by other entered into this study.  Keyword: Media Exposure, Vlog, Interest Making a Vlog.